Preventive Strategies for Radicalism Aspects of Religious Social Ideology through Child Religiosity in SD NU Metro Barat / Strategi Preventif Radikalisme Aspek Ideologi Sosial Beragama Melalui Religiusitas Anak di SD NU Metro Barat - Masrurotul Mahmudah; Ikhwan Aziz; Ismy Rahmadani (Al-Mudarris: Journal Of Education, 2020)
This study aims to provide information to parents in order to understand how to instill a better and more precise understanding of ideology in children through strategies established by schools with various excellent programs. There are several deviations from religious principles that are often applied to children by giving sweet promises in the form of jihad fi sabilillah (jihad for the sake of God Almighty) with guaranteed rewards and going to heaven for sure, truth does not necessarily know the truth. Many parents want their generation to be pious or pious under the pretext of being filial. In this study, the prevention strategy of children's radicalization was analyzed by practicing the religious dimension of students at West Metro NU Elementary School (Aspects of Religion Ideology and Social).The type of research used is descriptive analysis with two approaches, namely religious and social ideology. The technique of collecting data by means of interviews, observation and documentation. While the validity of the data uses data triangulation. Based on research data analyzed in depth, it shows that there is a need for a preventive strategy for children's radicalism in students at West Metro NU Elementary School (through aspects of religious ideology and social) is very important as information on the importance of understanding religious ideology in students so that it can maximize efforts to prevent the occurrence of radicalism. West Metro NU Elementary School promotes a moderate Islamic ideological system